QADE: a novel trust and reputation model for handling false trust values in e–commerce environments with subjectivity consideration - Zupancic, Eva; Trcek, Denis (Technological and Economic Development of Economy, 2017)
Trust is essential to economic efficiency. Trading partners choose each other and make decisions based on how much they trust one another. The way to assess trust in e-commerce is different from those in brick and mortar businesses, as there are limited indicators available in online environments. One way is to deploy trust and reputation management systems that are based on collecting feedbacks about partners’ transactions. One of the problems within such systems is the presence of unfair ratings. In this paper, an innovative QADE trust model is presented, which assumes the existence of unfairly reported trust assessments. Subjective nature of trust is considered, where differently reported trust values do not necessarily mean false trust values but can also imply differences in dispositions to trust. The method to identify and filter out the presumably false values is defined. In our method, a trust evaluator finds other agents in society that are similar to him, taking into account pairwise similarity of trust values and similarity of agents’ general mindsets. In order to reduce the effect of unfair ratings, the values reported by the non-similar agents are excluded from the trust computation. Simulations have been used to compare the effectiveness of algorithms to decrease the effect of unfair ratings. The simulations have been carried out in environments with varying number of attackers and targeted agents, as well as with different kinds of attackers. The results showed significant improvements of our proposed method. On average 6% to 13% more unfair trust ratings have been detected by our method. Unfair rating effects on trust assessment were reduced with average improvements from 26% to 57% compared to the other most effective filtering methods by Whitby and Teacy.First published online: 02 Jun 2015